Climate change injustice and school attendance and absenteeism: proximal and distal ecological links - Kearney, Christopher A.; Ellis, Kinsey; Arcaina, V. Jefferson (Frontiers in Education, 2024)
Climate change has been linked to a myriad of problems related to human functioning, with a particular scientific emphasis on economic, physical damage, and health sectors. Less attention, however, has been given to the links between climate change and problems in the educational sector, such as school attendance problems, which represent practical and everyday manifestations of the effects of climate change. This is unfortunate given that children, and particularly those in Black and Brown communities and in the majority world, are expected to bear the greatest burden from climate change now and in the future. One fundamental right of children is the right to an education and to attend school, and this right is threatened particularly for vulnerable populations in different ways by climate change. Narrative synthesis of key terms (e.g., climate change, school absenteeism) for literature review was conducted to identify key patterns that produced the primary themes represented in this article: physical health, mental health, violence, school environment, school displacement and migration, and economic challenges. These themes were organized along a general proximal-to-distal spectrum. The descriptions of each theme also illustrate mechanisms connecting these issues that may help inform future mitigation efforts.